The Effects Of A Low-Fat Diet And A Low-Carbohydrate Diet With Aerobic Exercise On Changing Of Lipid Profile - Ni Made Dewantari; I Wayan Ambartana; I Putu Suiraoka; GA Dewi Kusumayanti; Desak Putu Sukraniti; I Gede Iswara Pranidhana Putra (Indonesian Nutrition Association, 2020)
Lifestyle changes become the foundation in primary and secondary prevention of lipid and lipoprotein disorders. The aim of the study was to know the effectiveness of low fat diet and low carbohydrate diet with aerobic exercise toward lipid profile change. Type of experimental research with pre test-post test control group design. The sample of adult women in the city of Denpasar as many as 33 people, aged 30-50 years, IMT 25-30 kg/m2, allocated to 3 groups. Group 1 applied a low-fat diet, group 2 applied a low-carbohydrate diet and a group of 3 controls. Before and after the intervention a blood lipid profile was measured. Changes in blood lipid profile before and after intervention were analyzed by paired t-test. The difference in mean blood lipid profile in all three groups was analyzed by One Way Anova test. Low-fat diet and low-carbohydrate diet can lower total cholesterol and LDL-C significantly (p <0.05). The average decrease in total cholesterol with low fat diet was 16.82 mg/dL and low carbohydrate diet 14.64 mg/dL. Decreased LDL-C with a low-fat diet of 13.36 mg/dL and low-carbohydrate diet of 7.45 mg/dL. There was no significant difference in lipid profile changes between low fat diets compared to low carbohydrate diets (p>0.05). Thus a low-fat diet is as effective as a low-carb diet to improve lipid profile.Â